Problems of Teaching Engineering Graphics for the Architecture and Ways toSolve Them - Esekeshova M.D., Есекешова М.Д.; Tuleuova, Тулеуова Г.К. (Рroblems of engineering and professional education, 2022)
The article considers the actual problems of mastering the discipline "Engineering Graphics" associated with the low level of training of students and suggests ways to solve them by dividing the learning process into three stages: the teaching method, the teaching method and the control method.